1994
DOI: 10.1161/01.atv.14.12.1900
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized lipids in the diet are a source of oxidized lipid in chylomicrons of human serum.

Abstract: We examined whether oxidized lipids in the diet determine the levels of oxidized lipid in human postprandial serum chylomicrons. After we fed subjects control corn oil containing low quantities of oxidized lipid, the levels of conjugated dienes in the chylomicron fraction were low (9.67 ±0.92 nmol//imol triglyceride), and no thiobarbituric acid-reactive substances (TBARS) could be detected. However, when subjects were fed a highly oxidized oil, the conjugated diene content in chylomicrons was increased 4.7-fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
135
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(140 citation statements)
references
References 46 publications
2
135
0
1
Order By: Relevance
“…Subjects fed oxidized lipids have been reported to have elevated atherogenic oxidized lipids in postprandial chylomicrons, especially in the presence of diabetes (51,52). These reports, given the typical Western dietary patterns, may point indirectly to enhanced interactions between dietary lipids and AGEs.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects fed oxidized lipids have been reported to have elevated atherogenic oxidized lipids in postprandial chylomicrons, especially in the presence of diabetes (51,52). These reports, given the typical Western dietary patterns, may point indirectly to enhanced interactions between dietary lipids and AGEs.…”
Section: Discussionmentioning
confidence: 99%
“…The lipid composition of lipoproteins can vary significantly depending on the individual diet. Oxidized lipids in lipoproteins can originate from two sources; either fatty acids are oxidized or the oxidized lipids were taken up with the food and were incorporated into chylomicrons (44) and may contribute to atherosclerosis lesion formation (45). Besides fatty acid composition the pro-inflammatory activity of chylomicrons also depends on the content of plateletactivating factor acetylhydrolase (PAF-AH) activity and the availability of antioxidants like vitamin E. Lee et al (43) reported that although chylomicrons were relatively enriched in 18:1 fatty acids, which would make them less easily oxidized and thus less readily generate chemotactic activity they contained reduced levels of vitamin E per particle and no measurable PAF-AH activity.…”
Section: Proinflammatory Activitymentioning
confidence: 99%
“…10 Moreover, consumption of diets containing oxidized fatty acids also results in increased levels of oxidized lipids in the postprandial chylomicrons of humans. 13,14 Similar to fatty acids, dietary cholesterol is also easily oxidized 15,16 and is incorporated into serum lipoproteins in both animals [17][18][19][20] and humans. 21 Most importantly, we have recently shown that both oxidized fatty acids 22 and oxidized cholesterol 23 in the diet accelerate fatty streak formation in cholesterol-fed rabbits.…”
mentioning
confidence: 99%